Unveiling Malaysian parents' perspectives on existing quality of early childhood care and education - Tang, D.D. (LLC "Ecological Help", 2021)
Introduction. Early childhood care and education is majorly concerning around the world. Malaysian government has formulated childhood care and education national policy and legal framework to protect the rights of childhood. However, the Education Blueprint of Malaysia acknowledged that serious problems still remain with the quality of education and the investment in education is not as high as expected. The objective of the study is to investigate parents' perspectives of quality ECCE programs with regard to center characteristics of environment, teachers, principals, curriculum as well as parent's communication and involvement opportunities. Materials and methods. Study has selected mix method approach where parent perspectives of existing quality of early childhood care and education (ECCE) in the selected states of Malaysia been obtained. The 629 questionnaires samples were distributed among the parent 's having a child in a pre-school and 22 parents took part in the focus group interviews, designed to elicit their perspectives of ECCE programs with regard to center characteristics, environment, teachers, principals, and curriculum as well as parent involvement and communication opportunities Results. Demographically results shows 60.8 female and 39.2 male participants have contributed with 32 age 31-35 years old, about 38.1 Malay followed by 32.2 Chines and 18 Indian ethnicity races were part of this study. The standard deviation analysis indicated that Parents's perceptive on Centre Characteristics is (M=4.039, SD= 0.796) Parents' Views on Environment (M=3.582, SD=0.953); Parents' Views on Teachers and Principals (M=4.197, SD=0.731) Parents' Views on Curriculum ((M=3.735, SD=0.771) and Parents' Views on Parent Communication and Involvement Opportunities (M=4.171, SD=0.630). The overall statistical analysis shows parents' perceptive is satisfactory on the quality of ECCE programmes. Conclusion. Study has concluded that parents have found ECCE programmes much effective where children not only enjoy but their learning improves. Parents have appreciated the quality of hygiene level and facilities in pre-school are up to the mark and standard but further can be improved. Quality of curriculum should have multilingual instruction and play based teaching and learning is suggested by the parent's to improve. © 2021 LLC Ecological Help. All rights reserved.